Pelatihan Hypnoparenting untuk Meningkatkan Motivasi Orang Tua dalam Membimbing dan Mendidik Anak Usia 6 Tahun di TK Sumberwaru - Eliyawati, Eliyawati (Edujavare Publishing, 2026)
Parents play a crucial role in early childhood development; however, many face difficulties in providing effective guidance due to limited knowledge, low motivation, and ineffective communication patterns. This community service program aims to increase parental motivation in guiding and educating six-year-old children through hypnoparenting training at Sumberwaru Kindergarten. The community service method uses Participatory Action Research (PAR), with the program implemented through several stages, including preparation, training implementation, evaluation, and follow-up. The training method consists of interactive lectures, discussions, and practical sessions on hypnoparenting techniques. Evaluation was conducted using pre- and post-test instruments to measure parents' understanding and motivation before and after the training. The community service results showed an increase in parental knowledge and motivation in guiding and educating their children. Parents demonstrated increased awareness of the importance of positive communication, emotional control, and consistent involvement in their children's learning process. In conclusion, hypnoparenting training is an effective and applicable approach to increasing parental motivation and strengthening their role in early childhood education. This program is expected to contribute to ongoing collaboration between schools and parents in supporting child development.